Ecotoxicological assessment of silicate rock fertilizers using soil invertebrates - Niva, Cintia Carla (2021)
The objective of this work was to evaluate the possible adverse effects of rock dusts on the avoidance behavior of earthworms and collembolans, as well as on the survival and reproduction of enchytraeids, in ecotoxicological tests using artificial and natural soils. The tests were performed following international guidelines (ISO 17512-2/2011, ISO 11267/1999, and NBR ISO 16387/2012), with some adaptations, in order to evaluate the effect of dusts from two silicate rocks, biotite schist and phonolite, at the concentrations of 0, 0.1, 1.0, 10, and 100%, in artificial and natural (Arenosol and Ferralsol) soils. The avoidance behavior of the earthworm Eisenia andrei and the collembolan Folsomia candida was evaluated, as well as the survival and reproduction of the enchytraeid Enchytraeus sp. Biotite schist and phonolite affected negatively earthworms when applied to the soil at concentrations equal to or higher than 1.0%. The observed effect was associated to the greater presence of salts, especially in the phonolite, and to changes in soil texture when higher concentrations were used. Negative effects on collembolans and enchytraeids were verified at concentrations of 10% or using pure rock dusts. Agronomic rates smaller than 1.0% (approximately 20 Mg ha-1) rock dusts do not cause avoidance behavior or reduction in the survival and reproduction of invertebrates in the soil.